2009
DOI: 10.1093/humupd/dmp001
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of germ cells and gametes from stem cells

Abstract: Differentiation of germ cells from SCs has the potential of becoming a future source of gametes for research use, although further investigation is needed to understand and develop the appropriate niches and culture conditions. Additionally, if genetic and epigenetic methodological limitations could be solved, therapeutic opportunities could be also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 98 publications
1
57
0
4
Order By: Relevance
“…Standard culture conditions are unlikely to suffice, and advances in microfluidics may help to engineer a more physiological microenvironment. Oocyte-like cells were recently derived in culture from ES cells and various somatic cells, including the pancreas, fetal skin, and surfaces of human postmenopausal ovaries (137). While there is no doubt that germ cells can form in embryoid bodies from ES cells, culture conditions are still unable to recapitulate the specific and evolving conditions needed to generate a fertile oocyte, defined by the ability to produce a healthy baby.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Standard culture conditions are unlikely to suffice, and advances in microfluidics may help to engineer a more physiological microenvironment. Oocyte-like cells were recently derived in culture from ES cells and various somatic cells, including the pancreas, fetal skin, and surfaces of human postmenopausal ovaries (137). While there is no doubt that germ cells can form in embryoid bodies from ES cells, culture conditions are still unable to recapitulate the specific and evolving conditions needed to generate a fertile oocyte, defined by the ability to produce a healthy baby.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Also Hua et al reported the expression of meiotic markers (scp3) using testicular extraction and Retinoic Acid . Meiotic and post-meiotic markers are more reliable markers, but it has been demonstrated that the progression through the meiotic process is still a challenge in the in vitro differentiation of germ cells (Marques-Mari et al, 2009). Our work showed expression levels of Mvh, Id4 and Piwil2 genes and presence of Mvh and Scp3 proteins using Sustentacular cells condition medium for 48h.…”
Section: Discussionmentioning
confidence: 59%
“…The markers of early primordial GC (PGC) such as Stella, C-kit and Fragillis have key roles in GC competency and development, while Dazl and Vasa express in premeiotic GC. However, all these genes are also expressed in ES cells (Aflatoonian and Moore, 2006;Ko & Schöler, 2006;Nagano, 2007;Daley, 2007;Hua and Sidhu, 2008;Marques-Mari, 2009). Genetically modified ES cells using fluorescent proteins linked to specific gene promoters (genes implicated in pluripotency or GC line fate) have been used in order to pre-select committed PGC and to provide more efficient harvesting of mature GC (Hubner et al, 2003, Toyooka et al, 2003, Nayernia et al, 2006.…”
Section: Fig 2 Gametogenesismentioning
confidence: 99%
“…Several studies showed that ES cells in culture have already acquired the capacity to form PGC expressing a set of PGC genes in undifferentiated state e.g. PGC founder-specific genes Stella and Fragillis are detectable in ES cells before the onset of differentiation, whereas those genes are not expressed in the inner cell mass and early epiblast cells in vivo (Aflatoonian and Moore, 2006;Ko & Schöler, 2006;Nagano., 2007;Daley, 2007;Hua and Sidhu, 2008;Marques-Mari, 2009). The environmental factor can also influence the timing of differentiation, therefore progression of PGC differentiation may be suppressed in the embryonic environment until the PGC reach an appropriate position near the developing gonads.…”
Section: Timing Of In Vitro Es-derived Gc Differentiationmentioning
confidence: 99%